2022
DOI: 10.1093/ibd/izab334
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Crohn’s Disease Direct Costs in Health Care Systems (from Different Perspectives): A Systematic Review

Abstract: Background The prevalence of inflammatory bowel disease (IBD) has been increasing worldwide, causing high impact on the quality of life of patients and an increasing burden for health care systems. In this systematic review, we reviewed the literature concerning the direct costs of Crohn’s disease (CD) for health care systems from different perspectives: regional, economic, and temporal. Methods We searched for original real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
7
0
2
Order By: Relevance
“…costs. [29][30][31][32] With healthcare costs continuing to rise, biosimilars have the potential to improve access to biologics by providing less expensive treatment options with safety and efficacy profiles comparable to their RPs. 5,6 This study demonstrated PK equivalency in healthy volunteers following a single 90 mg SC injection of ABP 654, ustekinumab US, or ustekinumab EU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…costs. [29][30][31][32] With healthcare costs continuing to rise, biosimilars have the potential to improve access to biologics by providing less expensive treatment options with safety and efficacy profiles comparable to their RPs. 5,6 This study demonstrated PK equivalency in healthy volunteers following a single 90 mg SC injection of ABP 654, ustekinumab US, or ustekinumab EU.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of ustekinumab RP to control disease progression of patients with plaque psoriasis, psoriatic arthritis, Crohn's disease, and ulcerative colitis is well established 22–28 ; however, these conditions are associated with significant treatment costs 29–32 . With healthcare costs continuing to rise, biosimilars have the potential to improve access to biologics by providing less expensive treatment options with safety and efficacy profiles comparable to their RPs 5,6 …”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it would be very useful to develop international registries involving several countries currently experiencing a clear increase in the incidence of IBD, such as Latin America and Asia, and which have greater difficulty in accessing advanced treatments[ 50 - 52 ]. In this regard, the costs associated with dual therapy are the main limitation to access, which restrict the provision of a personalized treatment in patients with indication for this strategy[ 53 ]. Moreover, it is of great relevance to inform the health insurance of these patients about the objectives and advantages of the dual therapy strategy to obtain the appropriate approval in a timely manner for the indication.…”
Section: New Horizonsmentioning
confidence: 99%
“…Crohn's disease (CD) is a chronic inflammatory condition of the gastrointestinal tract with a remitting and relapsing course, 1 and substantial implications for the lives of patients, [2][3][4] as well as a considerable economic impact on society. 5 Current management strategies and therapies focus on reducing inflammatory burden in patients with active disease and maintaining remission in those with inactive disease. Over the last 20 years the efficacy of multiple novel drugs in inducing remission of active CD has been evaluated, mostly in randomized controlled trials (RCTs) versus a placebo.…”
Section: Introductionmentioning
confidence: 99%